The use of GPRs for identifing subsurface defects in road pavement - Батраков, Д. О.; Антюфеева, М. С.; Батракова, А. Г.; Хаоцзе, Фан (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2018)
The paper deals with the problem of positioning and identification of subsurface defects (cracks) in the lower layers of non-rigid type road pavements. Using the polarization state of probing and, respectively, reflected signals, that is the registration of the so-called cross-polarization signal components is proposed for the problem solution. Modified algorithms for determining the subsurface crack depth are proposed, as well as a comparative algorithm for estimating the width of a crack. The results of numerical modeling by developed software and the laboratory studies are presented. The experimental results of the road survey of the Kharkiv region are also presented